Transformasi Kurikulum Merdeka: Analisis Filosofis dan Implikasinya terhadap Pembentukan Karakter Peserta Didik - Budi Agung (Yayasan Albahriah Jamiah Indonesia, 2025)
The transformation of the Independent Curriculum is a response to the demands of globalization, the industrial revolution 4.0, and the emerging crisis of student character within the Indonesian education system. This curriculum promotes a differentiation-based approach, contextual learning, and the strengthening of the Pancasila Student Profile as the primary orientation for character formation. This study aims to philosophically analyze the rationale behind the Independent Curriculum and examine its implications for authentic student character development. The research method used is a descriptive qualitative study with a philosophical content analysis approach to official curriculum documents, educational theories, and relevant literature on character education. The results of the study indicate that the Independent Curriculum is rooted in the philosophies of progressivism and humanism, which position students as active, autonomous, and unique subjects in the educational process. The implementation of this curriculum allows for the transformative integration of moral, spiritual, and social values into learning activities. Its implementation provides space for teachers to adapt learning to students’ needs and potential, strengthens learning independence, and expands the school’s role as a character-building ecosystem. However, the results also indicate challenges in terms of teacher preparedness, unequal access, and consistent implementation in the field. The conclusions of this study confirm that the Independent Curriculum has great potential to shape students’ character holistically, provided it is supported by policies, teacher training, and ongoing evaluation.